THE EFFECT OF PERSONAL TENURE ON EARNINGS SURPRISE MANAGEMENT - Amelia, Devitha; Wardhani, Ratna (UI Scholars Hub, 2018)
The purpose of this study is to investigate the effect of personal tenure between Audit Partner and Client CEO on firm’s likelihood to do upward earnings management. Using non financial firms listed on Indonesia Stock Exchange period 2012 – 2014, this study finds that personal tenure between Audit Partner and Client CEO have significant positive influence on firms’ likelihood to do upward earnings management and downward forecast guidance. The results of this study indicate that personal tenure positively influences both mechanisms of avoiding negative earnings surprises. Furthermore, since the company's resources in doing both mechanisms are often limited, this study also examines the impact of personal tenure on firm’s choices between the two mechanisms, by testing whether companies choose to do downward forecast guidance, but not upward earnings management or using upward earnings management but not downward forecast guidance. The results show that personal tenure positively associated with the likelihood of firms doing downward forecast guidance without upward earnings management. The result indicates that lower independency of the audit partner due to longer tenure between Audit Partner and Client CEO encourage management to do earnings management by avoiding negative earnings surprise.